A Chimeric Peptide Inhibits Red Blood Cell Invasion by Plasmodium falciparum with Hundredfold Increased Efficacy. (23rd December 2022) - Mannuthodikayil, Jamsad; Sinha, Suman; Singh, Sameer; Biswas, Anamika; Ali, Irshad; Mashurabad, Purna Chandra; Tabassum, Wahida; Vydyam, Pratap; Bhattacharyya, Mrinal Kanti; Mandal, Kalyaneswar
Abstract: Inhibiting the formation of a tight junction between two malaria parasite proteins, apical membrane antigen 1 and rhoptry neck protein 2, crucial for red blood cell invasion, prevents progression of the disease. In this work, we have used a unique approach to design a chimeric peptide, prepared by fusion of the best features of two peptide inhibitors, that has displayed parasite growth inhibition ex vivo with nanomolar IC50, which is 100 times better than any of its parent peptides. Furthermore, to gain structural insights, we computationally modelled the hybrid peptide on its receptor. Abstract : A rationally designed peptide chimera, prepared by combining the best features of two known peptide inhibitors, displayed malaria parasite growth inhibition with a potency two orders of magnitude greater than that of any of its parent peptides.